PENGARUH PENGGUNAAN METODE PEER TUTOR DAN EFIKASI DIRI TERHADAP HASIL BELAJAR MATEMATIKA - Dailami Firdaus; Iffah Budiningsih; Sifah Fauziah (Akademika : Jurnal Teknologi Pendidikan, 2021)
The present study aims to identify the implementation of a peer-tutor method and self-efficacy towards the students’ mathematics learning outcomes. This experimental study involved two classes (each consisting of 35 students) as the research sample, which were extracted by a simple random sampling technique. Moreover, the data were analyzed by descriptive analysis, two-way ANOVA, and Tukey test. The study involved variables as follows: the peer tutor method was the experiment variable, the lecture method was the control variable, and the moderator variable was the self-efficacy indicator that was analyzed using instruments of learning outcomes test and questionnaire. The results reveal that: a) the learning outcomes of experiment class (peer tutor method) is higher than control class (lecture method); b) there is an interaction between the learning method and self-efficacy towards the learning outcomes; c) students with higher self-efficacy have higher learning results when taught by peer-tutor method compared to those who were taught by lecture method; d) for those with lower self-efficacy, both peer-tutor and lecture method generate similar learning results; e) for subjects like mathematics, peer-tutor method is suggested.